Role of Treg cell subsets in cardiovascular disease pathogenesis and potential therapeutic targets - Xia, Yuanliang; Gao, Di; Wang, Xu; Liu, Bin; Shan, Xue; Sun, Yunpeng; Ma, Dashi (Frontiers in Immunology, 2024)
In the genesis and progression of cardiovascular diseases involving both innate and adaptive immune responses, inflammation plays a pivotal and dual role. Studies in experimental animals indicate that certain immune responses are protective, while others exacerbate the disease. T-helper (Th) 1 cell immune responses are recognized as key drivers of inflammatory progression in cardiovascular diseases. Consequently, the CD4+CD25+FOXP3+ regulatory T cells (Tregs) are gaining increasing attention for their roles in inflammation and immune regulation. Given the critical role of Tregs in maintaining immune-inflammatory balance and homeostasis, abnormalities in their generation or function might lead to aberrant immune responses, thereby initiating pathological changes. Numerous preclinical studies and clinical trials have unveiled the central role of Tregs in cardiovascular diseases, such as atherosclerosis. Here, we review the roles and mechanisms of Treg subsets in cardiovascular conditions like atherosclerosis, hypertension, myocardial infarction and remodeling, myocarditis, dilated cardiomyopathy, and heart failure. While the precise molecular mechanisms of Tregs in cardiac protection remain elusive, therapeutic strategies targeting Tregs present a promising new direction for the prevention and treatment of cardiovascular diseases.